Diversifikasi Produk Mebel Lokal untuk Menguatkan Usaha Pariwisata Danau Bokuok di Desa Aursati - Nurdin; 'Audah, Safridatul; Morena, Yenita; Ermiyati; Fauzi, Manyuk; Saily, Randhi; Rurianti, Dwi Visti; Fakhri; Suprayogi, Imam; Gussyafri, Haji; Novan, Andre; Wibisono , Gunawan; Olivia, Monita (Pelita Masyarakat, 2026)
Aursati Village has considerable potential for the development of Danau Bokuok tourism, yet faces limitations in providing creative local products that reinforce the destination’s identity. The absence of facilities that showcase local characteristics has reduced the area’s attractiveness. This community service program aimed to strengthen tourism through the diversification of local furniture products utilizing wood waste and the natural forms of unproductive durian and rubber tree stumps. The program consisted of four stages: preparation through coordination and scheduling; program socialization and product education; technical training in crafting decorative furniture using local materials combined with resin; and the handover of products to the village for use as tourism support facilities. The results demonstrated improved knowledge, skills, and active participation of the community, particularly village youth, in creative production. The products developed not only offered aesthetic value but also reflected a strong local identity. This program is expected to stimulate sustainable village-based creative enterprises and foster a tourism-driven local economy. Moreover, the activity strengthened community awareness and a sense of ownership in tourism development, ensuring continued contributions and long-term impact.